Implementation Strategies of Halal Management Systems in the Food and Beverage Industry in Indonesia - Heri Kuncoro Putro (PAPUA: International Journal of Sharia Business Management, 2024)
The halal industry has emerged as a crucial sector in Indonesia, the country with the largest Muslim population in the world. With increasing global demand for halal-certified products, especially in the food and beverage sector, implementing a robust Halal Management System (HMS) has become essential for businesses aiming to meet consumer expectations and comply with national and international standards. This study explores the strategies for implementing HMS within Indonesia's food and beverage industry, focusing on challenges, opportunities, and best practices. Despite the growing awareness of halal compliance, many companies face difficulties in understanding and integrating halal standards into their operations. These challenges include insufficient knowledge, lack of skilled personnel, and complex certification processes. Moreover, companies often struggle to align their supply chain practices with halal requirements, ensuring the traceability and integrity of raw materials. However, implementing a structured HMS can enhance product quality, strengthen consumer trust, and expand market reach domestically and internationally. This study will analyze key strategies such as workforce training, technological integration for supply chain transparency, and collaboration with certification bodies to streamline compliance. By addressing these aspects, the research aims to provide actionable insights for businesses and policymakers to promote sustainable growth in Indonesia's halal food and beverage industry.